Perspectives on Slavery: The “Description of the Brooks Slave Ship” and the African Girl of Laurence Sterne’s Tristram Shandy - Britton, Jeanne (Romanticism on the Net, 2021)
This essay takes a new look at one of the most disturbing images of the Romantic period in order to reconsider the ethical significance of fictional episodes as they are resituated in Romantic-era literary anthologies. It uses the concept of the “diagram” to correlate the “Description of the Brooks Slave Ship” with anthologized versions of an episode from Laurence Sterne’s Tristram Shandy, and it finds in these different works a similar invitation for viewers or readers to fill in the blank spaces of printed texts. The image of the Brooks slave ship and Sterne’s episode involving a silent African girl expose, through the details of print, the functions that visual, narrative, and imaginative perspectives play in white authors’ representations of Black suffering.